2015
DOI: 10.1371/journal.pone.0134168
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Activated THP-1 Cells Infected with Mycobacterium tuberculosis Identifies Putative Clearance Biomarkers for Tuberculosis Treatment

Abstract: Biomarkers for determining clearance of Mycobacterium tuberculosis (Mtb) infection during anti-tuberculosis therapy or following exposure could facilitate enhanced monitoring and treatment. We screened for biomarkers indicating clearance of Mtb infection in vitro. A comparative proteomic analysis was performed using GeLC MSI/MS. Intracellular and secreted proteomes from activated THP-1 cells infected with the Mtb H37Rv strain (MOI = 1) and treated with isoniazid and rifampicin for 1 day (infection stage) and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…The discovery of Mtb clearance markers that can be used as TB treatment monitoring markers is difficult in part because of the difficulty of confirming clearance of Mtb from the tissues of patients. Previously, we successfully demonstrated that THP-1 cells infected with Mtb strain H37Rv could be treated with anti-TB drugs leading to confirmed in-vitro clearance of bacilli [13]. With a simple cell-line model, we demonstrated that SSFA2, NCOR2, MCM2, RANBP1, RPTN, ELFN1, RFC2, SETX and CEACAM18 were potential clearance biomarkers [13].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The discovery of Mtb clearance markers that can be used as TB treatment monitoring markers is difficult in part because of the difficulty of confirming clearance of Mtb from the tissues of patients. Previously, we successfully demonstrated that THP-1 cells infected with Mtb strain H37Rv could be treated with anti-TB drugs leading to confirmed in-vitro clearance of bacilli [13]. With a simple cell-line model, we demonstrated that SSFA2, NCOR2, MCM2, RANBP1, RPTN, ELFN1, RFC2, SETX and CEACAM18 were potential clearance biomarkers [13].…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we successfully demonstrated that THP-1 cells infected with Mtb strain H37Rv could be treated with anti-TB drugs leading to confirmed in-vitro clearance of bacilli [13]. With a simple cell-line model, we demonstrated that SSFA2, NCOR2, MCM2, RANBP1, RPTN, ELFN1, RFC2, SETX and CEACAM18 were potential clearance biomarkers [13]. In the current study, we used a more complex model with stringent criteria to select candidate clearance biomarkers that could be used clinically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The breast was considered an organ that offers resistance to the survival and multiplication of the tubercle bacillus [24], like other organs such as spleen, skeletal muscle or cervix uteri, and this property is one of the reasons for the uncommon diagnosis of breast TB, and in countries like India it is supposed that the breast TB is confused to carcinoma [25], or to a pyogenic breast abscess [26], or to other diseases [27], tubercular mastitis being a "great masquerader" [28]. In contrast to this quality, when breast is infected with MbT, it was proved that BRCA 1/2 network is suppressed during infection suggesting that breast cell proliferation suppression is a feature of Koch bacilli survival [29].…”
Section: Pathophysiology Of Breast Tuberculosismentioning
confidence: 99%